From Children's Book to Film: A Study of Adaptation of Peter Rabbit - Akhmad Suwistyo (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2023)
The success of films adapted from literary works, including children's books in captivating audiences and dominating international cinema motivates this article. As a result, it is critical to comprehend how The Theory of Adaptation is applied to adapt literary works into the visual framework of the film. According to certain adaptation models given by experts, adaptation of a literary work such as a children's book into film can be done in two ways: first, by focusing on fidelity to the source, and second, by taking the source's contextuality and intertextuality into account.